Discourse of silence - Kurzon, Dennis (Pragmatics & beyond, 1998)
The book deals initially with the interpretation of the silent answer to a question. From a semiotic approach to the contrast between silence and speech mainly within a Greimasian framework, the discussion turns to the application of pragmatic tools such as conversational analysis and adjacency pairs to the interpretation of silence. A model is presented which attempts to explain the observer's cognitive competence, and its limits, in being able to interpret the silent answer. A basic distinction is also made between intentional silence (the refusal to answer) and non-intentional silence (the.